TECHNOLOGY INTEGRATION IN ENGLISH LANGUAGE TEACHING: TOOLS AND TECHNIQUES - Safarova Dildora; Saidova Dilobar; Shukurbekova Nafisa (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article explores the integration of technology in English language teaching (ELT) by analyzing modern tools and techniques that enhance the learning experience. It discusses Learning Management Systems (LMS), online dictionaries, interactive mobile applications, AI-powered writing assistants, speech recognition tools, and gamification as effective digital solutions for improving language acquisition. Additionally, various teaching methodologies, such as blended learning, the flipped classroom approach, and the use of virtual reality (VR), are examined. The article also addresses potential challenges related to technology integration, including accessibility issues, teacher training, and balancing traditional and digital teaching methods.